2008
DOI: 10.5194/angeo-26-517-2008
|View full text |Cite
|
Sign up to set email alerts
|

Optical, radar, and magnetic observations of magnetosheath plasma capture during a positive IMF <I>B<sub>z</sub></I> impulse

Abstract: Abstract. We present a multi-instrument study of the ionospheric response to a northward turning of the IMF. The observations were made in the near-noon (11:00 MLT) sector on Svalbard (at 75 • MLAT). The data set includes auroral observations, ionospheric flows obtained from the EISCAT and CUTLASS radars, the spectral width of the HF radar backscatter, particle precipitation and plasma flow data from the DMSP F13 satellite, and Pc1 frequency band pulsations observed by induction magnetometers. Careful collocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…The broadening of spectral lines in SuperDARN radar backscatter is frequently considered as a signature of the cusp (e.g., Chisham et al, 2005), though in some cases, especially during northward or near-zero IMF B z (Safargaleev et al, 2008), a large spectral width was observed on both open and closed field lines. The region of increased spectral width may also include closed LLBL or other turbulent precipitation regions, which has been shown by Villain et al (2002).…”
Section: Annmentioning
confidence: 99%
See 1 more Smart Citation
“…The broadening of spectral lines in SuperDARN radar backscatter is frequently considered as a signature of the cusp (e.g., Chisham et al, 2005), though in some cases, especially during northward or near-zero IMF B z (Safargaleev et al, 2008), a large spectral width was observed on both open and closed field lines. The region of increased spectral width may also include closed LLBL or other turbulent precipitation regions, which has been shown by Villain et al (2002).…”
Section: Annmentioning
confidence: 99%
“…The difference in the cusp detection by SuperDARN radars in Hankasalmi and Goose Bay is probably related to their different beam orientation to the cusp. Additionally, we tried to use particle precipitation data from DMSP satellites, which are a reliable means to obtain the cusp location (Safargaleev et al, 2008). Though for all the analyzed events the DMSP tracks were rather far from the meridian under examination, a tendency was observed that maximal ULF activity was situated around the CPS/LLBL interface, though sometimes shifted into the region of the ionospheric projection of the CPS or LLBL.…”
Section: Annmentioning
confidence: 99%
“…The concept of lobe reconnection was supported by case studies using in-situ spacecraft measurements (Onsager et al, 2001) and ground based observations (Pryse et al, 2006). The expected consequences of such plasma capture are poleward displacements of the cusp and the open/closed field line boundary (OCFLB) near noon (Safargaleev et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although such a multi-instrumental approach reduces the number of "optical events" suitable for analysis and turns them into so-called "case-studies", it makes the interpretation of observations less uncertain (e.g. [1]).…”
Section: Introductionmentioning
confidence: 99%
“…There are several case studies (e.g. [14,15,1]) demonstrating the possible association of auroras with some domains but reliable statistics are not available so far. The situation can not be clarified using aurora observations from satellites such as Viking, Polar or Image because they give only an overview of auroral activity due to low spatial/temporal resolution, as well as low sensitivity of onboard optical instruments.…”
Section: Introductionmentioning
confidence: 99%